2011
DOI: 10.1002/jso.21922
|View full text |Cite
|
Sign up to set email alerts
|

Biological reconstruction using massive bone allograft with intramedullary vascularized fibular flap after intercalary resection of humeral malignancy

Abstract: Intramedullary fibular flaps in combination with massive allografts provide an excellent option for reconstruction of large bony defects after humeral malignancy extirpation. The viability of the fibula is a cornerstone in success of reconstruction that prevents allograft nonunion and result in decreased time to bone healing, leading to earlier patient recovery and return of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 52 publications
1
34
0
2
Order By: Relevance
“…The complication rate in the intercalary group (53%) was lower than in the other groups—albeit not statistically significant ( P = 0.622). Li et al found a comparable complication rate of 43% in intercalary allograft and vascularized fibula construct, with no fractures. Likewise, Aponte‐Tinao et al found no fractures in their intercalary group either and concluded that intercalary allograft had the lowest complication rate and best mean function score compared to osteoarticular allografts and APC.…”
Section: Discussionmentioning
confidence: 95%
“…The complication rate in the intercalary group (53%) was lower than in the other groups—albeit not statistically significant ( P = 0.622). Li et al found a comparable complication rate of 43% in intercalary allograft and vascularized fibula construct, with no fractures. Likewise, Aponte‐Tinao et al found no fractures in their intercalary group either and concluded that intercalary allograft had the lowest complication rate and best mean function score compared to osteoarticular allografts and APC.…”
Section: Discussionmentioning
confidence: 95%
“…The devitalized bone graft provides bone stock and initial mechanical stability, and VFG substantially not only promotes bone union of the host‐graft junction, but also enhances neo‐vascularization to the dead, grafted bone, which provides osteoblastic and osteoclastic progenitor cells . Li et al noted that the healing process between VFG and the host bone occurred in a fashion identical to that seen in normal fracture healing, without creeping substitution . In addition, a recent study demonstrated that the additional use of VFG enhanced histological repair in heat‐treated autografts as assessed by histological examination .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [16] observed that abundant callus originated from the outlayer of the fibula that union the fibula with the host bone and allograft together. Pasteurized autogenous bones are similar to allografts, in that both possess bone induction ability and bone conductive ability [14].…”
Section: Discussionmentioning
confidence: 99%